Development of a multiplex real-time PCR to differentiate the four major Listeria monocytogenes serotypes in isolates from meat processing plants. (May 2020) - Alía, Alberto; Andrade, María J.; Córdoba, Juan J.; Martín, Irene; Rodríguez, Alicia
Abstract: Listeria monocytogenes is an important foodborne pathogen, causative agent of listeriosis. The epidemiology and persistence of this bacterium in meat processing plants may be related to its serotype, so it is of utmost importance to carry out a correct differentiation of L. monocytogenes serotypes. The objective of this study was to develop a unique quadruplex real-time quantitative PCR (qPCR) method able to differentiate the four most predominant and worrying L. monocytogenes serotypes (1/2a, 1/2b, 1/2c and 4b) in isolates from meat processing plants and ready-to-eat (RTE) dry-cured meat products. The design of specific primers and probes was based on the lmo0737, lmo0308, ORFC (locus genomically equivalent to gltA-gltB ) and ORF2110 genes. A qPCR based on a fragment of the 16S rRNA gene was used to ensure the amplification of Listeria spp. genomic DNA. The standard curves showed efficiency values ranging between 92.3% and 105.8% and, R 2 values > 0.98. The specificity of the method was also confirmed by the comparison of the results with those obtained by a previously reported conventional multiplex PCR. In addition, none of the strains which were not ascribed to L. monocytogenes amplified any of the target genes related to the four major serotypes of this pathogenic species. The qPCR, therefore, provides a sensitive, specific and rapid tool for identifying the L. monocytogenes serotypes 1/2a, 1/2b, 1/2c and 4b. This method could be very useful for identifying sources of L. monocytogenes contamination in the meat industry or for epidemiological monitoring of persistent strains throughout the processing of RTE meat products. Highlights: A multiplex qPCR to differentiate the four main L. monocytogenes serotypes was optimised. Lmo0308, lmo0737, ORFC and ORF2110 genes were targeted for serotype differentiation. Serotypes by PCR matched with those obtained by the developed multiplex qPCR. The designed qPCR is an efficient tool to differentiate L. monocytogenes serotypes.